A novel TP63 variant in a patient with ankyloblepharon-ectodermal defect–cleft lip/palate syndrome and Rapp–Hodgkin syndrome-like ectodermal dysplasia - Asuka Hori (Human Genome Variation, 2022)
Abstract Ankyloblepharon-ectodermal defect–cleft lip/palate syndrome and Rapp–Hodgkin syndrome are well-known TP63-related autosomal-dominant genetic disorders with various similar ectodermal dysplasias. In this study, whole-exome sequencing revealed a novel, potentially pathogenic TP63 nonsense variant (NM_001114980.2:c.25 C > T: p.Gln9Ter) in a patient with an atypical clinical phenotype. This variant was detected near translation initiation sites and has an effect only on ΔNp63α, the short isoform protein product of the TP63 gene.